CARDIORRESPIRATORY FITNESS AND FAT PERCENTAGE OF YOUNG SOCCER PLAYERS OF A TEAM FROM CRATO CITY, CEARÁ-BRAZIL (Fiep Bulletin - online, 2011)
This study aimed to identify levels of cardiorespiratory fitness and relative body fat (BF%) in children and adolescents football city of Crato, Ceará. The study is characterized as a descriptive-exploratory study with a quantitative field. With sample was intentional voluntary, composed of 34 male adolescents with average age of 14,14 ± 2,00 years. To assess the variables general resistance test of walking and running 9 minutes proposed by the battery PROESP-BR and the level of adiposity and body fat percentage, it was decided by the equation proposed by Boileau et al. (1985). People make a database in Microsoft Excel 2007 for Windows®, to analyze the results we resort to descriptive statistics and Z-scores and correlation "r" coefficient. The results show that resistance in general our group presented an mean 1783,8 ± 308,8 with Z-scores of 2.06, this shows that our youth had scores considered as excellent. The values of fat on the group presented an mean 12,5 ± 3,2, but the Z score (Z =- 2,96) was considered very weak. The general resistance when compared to the classification proposed by PROESP-BR, showed adequate levels of 91,2% and the fat on the classification of Lohman was classified as excellent and low in 94,1% of the time. We found a correlation between resistance and general age (r = 0,786). The results show that young people, within the parameters of health, meet satisfactory levels in both the component of resistance in general and relative fat when compared to other studies. Parameters in the athletic results were not satisfactory. But these results need further clarification and analysis, since the literature is still scarce in studies related to this age group as well as playing football, using the Z score as a criterion of analysis.
Keywords: cardiorespiratory fitness; body fat; young; football